Validation of a Simple Extraction Procedure for Stimulants Identification from Human Plasma - Idha Arfianti Wiraagni1-4, Mustafa Ali Mohd2 , Rusdi Abdul Rashid3, Didi Erwandi bin Mohamad Haron2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
In this study, a novel LC-MS/MS (Liquid Chromatography-Tandem Mass Spectrometry) method wasdesigned using a simple extraction procedure that was scientifically developed to capture the most relevantstimulants, methamphetamine, MDA (3,4-Methylenedioxyamphetamine), MDMA (3,4-Methylenedioxymethamphetamine), and MDEA (Methyl diethanolamine). The LC-MS/MS method was validated usingUS FDA (United States Food and Drug Administration) guidelines, and all validation requirements weresatisfactory. This protein precipitation method was specifically developed for handling large numbers ofsamples with minimum cost and volume of sample. The developed method was accurate, precise, andreproducible for quantification of stimulant from human plasma. This pilot study enrolled 100 drug addictsto evaluate stimulant testing from plasma. Our findings found 47 cases with positive methamphetamine.This method may be valuable for stimulant blood screening for a large and varied population because of itsefficiency and economical aspects.